Dekonstruksi YOLO: Carpe Diem Pengkhotbah 11:9 atas Kecemasan Eksistensial Generasi Muda - Lidiah Lidiah; Kornelius Rulli Jonathans; Philip Suciadi Chia (Sekolah Tinggi Teologi Sumatera Utara, 2026)
The cultural phenomenon of YOLO (You Only Live Once) reflects the mindset of the younger generation, which emphasises freedom and prioritises temporary pleasures. This gives rise to anxiety due to a loss of direction in life, which is exacerbated by the dominance of internet technology, social media and digital culture. The church and Christian education face a major challenge in reinterpreting the value of life among a generation that is thirsty for meaning but trapped in a cycle of instant gratification. The phenomenon among young people highlights the need for theological reflection on the value of Carpe Diem in the light of the Christian faith. This study aims to deconstruct the understanding of YOLO through a hermeneutic reading of Ecclesiastes 11:9 in order to rediscover the spiritual meaning in freedom of life. It uses a descriptive qualitative method with a hermeneutic approach and literature study. It can be concluded that the YOLO spirit in the culture of the digital generation reflects an existential crisis that arises from a loss of meaning in life and spiritual orientation amid the tide of hedonism and technology. Through theological deconstruction of Ecclesiastes 11:9, it is found that true Carpe Diem is not unlimited freedom, but joy lived in awareness of God and moral responsibility. The implications of this study emphasise the importance of church education oriented towards the formation of reflective spirituality, spiritual resilience, and digital wisdom for today's young generation.AbstrakFenomena budaya YOLO (You Only Live Once) mencerminkan cara berpikir generasi muda yang menekankan kebebasan dan memprioritaskan kenikmatan sementara. Sehingga memunculkan kecemasan akibat kehilangan arah hidup yang diperkuat oleh dominasi teknologi internet, media sosial dan budaya digital. Gereja dan pendidikan Kristen menghadapi tantangan besar untuk menafsirkan ulang nilai hidup di tengah generasi yang haus makna, namun terjebak dalam siklus kepuasan sesaat. Fenomena di kalangan muda menunjukkan perlunya refleksi teologis terhadap nilai Carpe Diem dalam terang iman Kristen. Penelitian ini bertujuan untuk mendekonstruksi pemahaman YOLO melalui pembacaan hermeneutik terhadap Pengkhotbah 11:9 agar ditemukan kembali makna spiritual dalam kebebasan hidup. Menggunakan metode kualitatif deskriptif dengan pendekatan hermeneutik dan studi pustaka. Sehingga dapat disimpulkan bahwa semangat YOLO dalam budaya generasi digital mencerminkan krisis eksistensial yang muncul akibat kehilangan makna hidup dan orientasi spiritual di tengah arus hedonisme dan teknologi. Melalui dekonstruksi teologis terhadap Pengkhotbah 11:9, ditemukan bahwa Carpe Diem sejati bukanlah kebebasan tanpa batas, melainkan sukacita yang dijalani dalam kesadaran akan Allah dan tanggung jawab moral. Implikasi penelitian ini menegaskan pentingnya pendidikan gereja yang berorientasi pada pembentukan spiritualitas reflektif, ketahanan rohani, dan kebijaksanaan digital bagi generasi muda masa kini.